Os efeitos de um programa de exercício na capacidade física, função muscular periférica, qualidade de vida e processo inflamatório em crianças e adolescentes asmáticos: um ensaio clínico randomizado e controlado - Reimberg, Mariana Mazzuca (2018)
The effects of asthma cause a reduction in exercise tolerance in the pediatric population. However, multidimensional aspects of pulmonary rehabilitation (PR) such as exercise capacity, peripheral muscle strength (PMS), physical activity in daily life (PADL) and quality of life (QOL) were not studied in a single trial clinical. Objective: To evaluate the effects of PR on physical and functional capacity, PMS, PADL and inflammatory profile in asthmatic children and adolescents, under medical supervision. Methods: Randomized and controlled study in asthma patients, divided into intervention group (IG n=38, 10±3 years) who underwent aerobic training (Intensity 60-80% of heart rate (HR) in Incremental Shuttle Walk Test - ISWT), muscle strength training (40-70% of 1MR) and control group (CG n=38, 11±3 years) who underwent stretching exercises. Both underwent a supervised program twice a week for two months and sixty minutes per session. Evaluations were performed at the beginning and at the end of the study. Spirometry was performed before and after bronchodilator. The primary outcomes were: the load (W) in the cardiopulmonary exercise test (CPET): cycle ergometer; distance walked (DW) in ISWT; PMS of biceps brachii (BB) and quadriceps femoris (QF), evaluated by maximum voluntary isometric contraction (MVIC) and submaximal (SIC) per load cell; AFVD was evaluated by the percentage of time spent in mild and sedentary activities (% SLPA) and intense (% MVPA), as well as the number of steps (NP), by accelerometry (5 days of use and more than 8h/day), QOL by Pediatric Asthma Quality of Life Questionnaire (PAQLQ), asthma control by ACT and C-ACT and inflammatory profile (IL-4, IL-5, IL-10, IL-13, IL-17 and TNF-alpha). The data were represented as the difference post and pre intervention. Results: all volunteers were classified with mild asthma, according to the Global Initiative for Asthma (GINA): IG 2(1-3) vs CG: 2(1-3), p=0.73; and there was no change in lung function. After the protocol, the IG presented improvement in the predicted% of CPET load (p=0.01). There was no difference in the DW of the ISWT between the groups (p=0.73), however the IG increased the DW after PR: 36m(6.4-65.3) vs CG 28m(-0.5-58.2), p=0.01. There was no difference in PMS, PADL, QOL and in the inflammatory profile after PR, however, the IG improved the clinical control of the disease according to the asthma control questionnaire and went from partially controlled asthma to controlled (p=0.01). Conclusion: Two months of PR program, twice a week in children and adolescents with asthma under medical supervision, can improve exercise tolerance and clinical control of the disease without altering the behavior of PADL.